Antibacterial and cytotoxic activities of supernatant and mycelium extracts from fermentation of fungal symbiont Trichoderma reesei TV221 - Putu Oka Samirana&, Yosi Bayu Murti, Riris Istighfari Jenie, Erna Prawita Setyowati (Journal of Applied Pharmaceutical Science, 2021)
Fungi are microorganisms that can be in a symbiotic relationship with marine sponges in producing secondary metabolites. One of the sponge-associated fungi that have been studied and have antibacterial and cytotoxic activity is Trichoderma reesei TV221. This fungus comes from the Stylissa flabelliformis sponge from Menjangan Island, West Bali National Park, Bali. This study aimed to determine the growth curve of fungi fermented with seawater made from natural sea salt with a concentration of 30 parts per trillion (ppt), to be tested for antibacterial and cytotoxic activities on the mycelium and supernatant components of the fermentation, and to determine the selectivity index (SI). The growth curve was plotted by determining the dry weight of the mycelium every 2 days for 14 days of fermentation. The antibacterial activity of the extract was tested against Escherichia coli American Type Culture Collection (ATCC) 25922 and Staphylococcus aureus ATCC 25923, while the cytotoxic activity was tested against the WiDr cancer cell line and Vero cell line. The results showed that the maximum growth of T. reesei TV221 fungi took place on day 12. The mycelium and supernatant extracts from the fermentation had a potential antibacterial activity, especially against S. aureus ATCC 25923, especially fermentation on days 6 and 12. The supernatant extracts on days 12 and 14 had potential cytotoxic activity against the WiDr cancer cell line and had an SI value > 3. Based on the antibacterial and cytotoxic activities, it is likely that the active metabolites of the T. reesei TV221 fungus began to be produced on day 2 and reached their peak on day 12. The active metabolites contributing to the antibacterial and cytotoxic activities were estimated to be cyclohexanone, phenol, and terpenoid groups.
Keywords: Trichoderma reesei, antibacterial, cytotoxic, fermentation, salinity